2022
DOI: 10.1590/1806-9479.2021.229595
|View full text |Cite
|
Sign up to set email alerts
|

Applying analytic hierarchy process (AHP) to identify decision-making in soybean supply chains: a case of Mato Grosso production

Abstract: This paper aims to identify and analyze the factors that influence the decision of Mato Grosso’s farmers to produce soybean using the Analytic Hierarchy Process (AHP). We found evidence that decision-making of soybean production is related to rural production aspects such as climate, financing, cost of inputs, and soil quality rather than marketing and logistics. The novelty of this paper is the empirical analysis of the decision-making in agricultural production using AHP. The decision model was created and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
2
0
2
Order By: Relevance
“…Their study provided valuable insights for producers. In our study case, the maps indicated that farmers should be more concerned about E. heros in the northern and Midwest regions; the latter includes the state of Mato Grosso, the largest producer of soybean and corn in Brazil (Toloi et al 2022).…”
Section: Discussionmentioning
confidence: 81%
“…Their study provided valuable insights for producers. In our study case, the maps indicated that farmers should be more concerned about E. heros in the northern and Midwest regions; the latter includes the state of Mato Grosso, the largest producer of soybean and corn in Brazil (Toloi et al 2022).…”
Section: Discussionmentioning
confidence: 81%
“…This application can integrate expert opinions and does not limit hierarchical levels or the number of levels. Explanation of strategies for reducing health impacts and determining the value of the questionnaire which includes regulatory, economic, environmental, and social aspects [8].…”
Section: Methodsmentioning
confidence: 99%
“…The results found that knowledge sharing from farmers to consumers is important; however, knowledge from farmers should be considered and relevant information selected before sharing with consumers. Toloi et al (2022) identified and analyzed the factors that influence the farmers' decision to produce soybeans using the AHP. The evidence showed that decision-making in soybean production is related to rural production aspects such as climate, financing, cost of inputs, and soil quality rather than marketing and logistics.…”
Section: Literature Reviewmentioning
confidence: 99%